THE ROLE OF TOURISM IN SOCIO-ECONOMIC INTEGRATION IN THE CONTEXT OF GLOBALIZATION (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
It is well known that the processes of globalization are steadily advancing social, political, and economic cooperation. Tourism is considered an integral part of this process, serving as a medium for dialogue between cultures and playing a crucial role in shaping relationships between nations and peoples. From this perspective, this article aims to explore the origin and historical development (genesis) of tourism by analyzing various definitions of the concept found in literary sources.